Hubungan Kondisi Jamban dan Perilaku Sanitasi Lingkungan terhadap Kejadian Diare di Wilayah Belawan Sicanang - Nanda, Meutia; Yustika, Dilla; Lubis, Alvi Hazri; Maipina, Data Rizqueen; Pralistami K,, Fitri; Putri, Karina Aulia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
One of the environment-based diseases is diarrhea. This disease is closely related to environmental sanitation conditions such as inadequate latrines and garbage. The World Health Organization (WHO) states that there are at least 2.2 million people who die from diarrhea, this is related to environmental conditions (sanitation/hygiene) and inadequate water (Moernanto, 2009). Judging from the district's health profile in 2018 it stated that in North Sumatra there were cases of diarrhea at all ages, namely 11,151 cases with service coverage reaching 10,280 cases (92.19%). Method: The design used in this study is descriptive quantitative with a cross sectional approach, and the research location is the Belawan Sicanang area. The number of research samples is 69 respondents using a non-probably sampling technique, namely the accidental sampling technique. Results: Based on the results of the SPSS analysis research based on the chi-square test with α=5%, it can be stated that there is a relationship between the location of the existence of latrines, the use of clean water, and the behavior of disposing of garbage to the TPA with the incidence of diarrhea in Belawan Sicanang with the acquisition of a Pvalue of each 0.03, 0.015, and 0.02 (p<0.05). Keyword: Diarrhea, healthy latrines, environmental sanitation